SYTHESIS OF SOME 6-BROMO QUIAZOLIOE DERIVATIVES FOR THEIR PHARAMCOLOGICAL ACTIVITIES. - CH.RAJVEER; D.KUMARASWAMY; S.SUDHARSHINI; B.STEPHEN RATHINRAJ (International Journal of Pharma and Bio Sciences, 2010)
A number of substituted 6-bromoquinazolinones are known for their pharmacological importance like anti-inflammatory, analgesic and anti-bacterial activity. In the present investigation is carried out for the synthesis of 2-(6-bromo-2-phenyl-4-oxoquinazolin-3(4H)-yl)-N-substituted acetamides and 1-Amino-5-(6- bromo-3, 4-dihydro-2-phenyl-4-oxoquinazolin-3yl) methyl-1, 3, 4-triazin-2-thiol to carry out their pharmacological activities. A number of oxoquinazoline derivatives have been synthesized, purified and characterized with the help of their analytical and spectral data (IR, NMR & Mass).The required ethyl [6-bromo- 2-phenyl-4-oxoquinazolin-3(4H)-yl] acetate has been synthesized from 6-bromo-2-phenyl-1,3,4-benzoxazinone and ethyl glycinate. By the use of corresponding primary amines the N-substituted acetamides and by the use of hydrazine hydrate the 1-amino-5-[6-bromo-2-phenyl-4-oxoquinazolin-3(4H)-yl] methyl 1, 3, 4-triazin-2-thiol were prepared. The synthesized compounds were screened for their anti-bacterial activity, anti-inflammatory activity and analgesic activity by standard methods. The compound shows Pharmacological activities in comparison with the standard.